Dramatic Monologue in T. S. Eliot’s The Love Song of J. Alfred Prufrock - Karo, Hasan (Humanities Journal of University of Zakho, 2022)
This paper discusses the use of ‘dramatic monologue’ and ‘stream of consciousness’ in T. S. Eliot’s “The Love Song of J. Alfred Prufrock”. It highlights the history of the two terms with references to certain lines of the poem. It unveils the effect of using such a technique by Eliot. The paper investigates how the speaker ‘J. Alfred Prufrock’ is trying to communicate with the reader in dramatic monologue. Furthermore, it examines how J. Alfred Prufrock’s brain and process of thoughts is working through the use of stream of consciousness and interior monologue to achieve such process of thoughts. The paper pays all the attention to main character’s language to answer the research’s question in which makes the paper a discourse analytic research. The main question that the paper raises is how Prufrock’s behavior explains the existence of dramatic monologue within himself. It is worth mentioning that the paper’s conclusion provides the findings of the research.